The Impact of Poor Nonverbal Social Perception on Functional Capacity in Schizophrenia - Chapellier, Victoria; Pavlidou, Anastasia; Maderthaner, Lydia; von Känel, Sofie; Walther, Sebastian (Frontiers in Psychology, 2022)
Background: Nonverbal social perception is the ability to interpret the intentions and dispositions of others by evaluating cues such as facial expressions, body movements and emotional prosody. Social perception plays a key role in social cognition and is fundamental for successful social interactions. Patients with schizophrenia have severe impairments in social perception leading to social isolation and withdrawal. Collectively, this deficit affects patients’ quality of life. Here, we compare social perception in patients with schizophrenia and controls and examine how social perception relates to daily functioning. Methods: We compared nonverbal social perception in 41 stable outpatients with schizophrenia and 30 healthy controls using the Mini Profile of Nonverbal Sensitivity (Mini-PONS). The participants evaluated 64 video clips showing a female actor demonstrating various nonverbal social cues. Participants were asked to choose one of two options that best described the observed scenario. We correlated clinical ratings (Positive and Negative Syndrome Scale, Brief Negative Syndrome Scale), Self-report of Negative Symptoms, and functional assessments (functional capacity and functional outcome) with total Mini-PONS scores. Results: Patients performed significantly poorer in the Mini-PONS compared to controls, suggesting deficits in non-verbal social perception. These deficits were not associated with positive symptoms, negative symptoms, symptom severity in patients, as well as, self-report of negative symptoms. However, impaired nonverbal social perception deficits correlated with some distinct negative symptom domains, functional capacity and functional outcome in patients. Conclusion: We demonstrate that nonverbal social perception is impaired in stable outpatients with schizophrenia. Nonverbal social perception is directly related to some negative symptom domains, functional capacity and functional outcome. These findings underline the importance of nonverbal social perception for patients’ everyday life and call for novel therapeutic approaches to alleviate nonverbal social perception deficits.